5-Fluorouracil in the Treatment of Keloids and Hypertrophic Scars: A Comprehensive Review of the Literature. Issue 2 (June 2016) - Shah, Vidhi; Aldahan, Adam; Mlacker, Stephanie; Alsaidan, Mohammed; Samarkandy, Sahal; Nouri, Keyvan
Abstract Hypertrophic (HTSs) and keloid scars are common dermatological complaints produced by disruption of the normal wound-healing process. Despite a wide array of therapeutic options available to treat these lesions, HTSs and keloids continue to pose a significant challenge to clinicians in everyday practice. The chemotherapeutic drug 5-fluorouracil (5-FU) is a well-known treatment option reserved for recalcitrant HTSs and keloid lesions. We present clinicians with a comprehensive review of the published data concerning the use of 5-FU in the treatment of HTSs and keloids. The current evidence suggests that 5-FU is a safe and practical alternative for the treatment of HTSs and keloids as it may substantially improve the appearance of proliferative scars and reduce the chance of recurrence. This therapeutic option is most effective in conjunction with adjuvant therapy such as corticosteroids. Additional randomized controlled clinical trials with large sample sizes should be conducted to corroborate the existing efficacy and safety data in patients with HTSs and keloids.